2016
DOI: 10.1039/c6ce00059b
|View full text |Cite
|
Sign up to set email alerts
|

Coordination networks incorporating halogen-bond donor sites and azobenzene groups

Abstract: a Two Zn coordination networks, {[ZnIJ1)IJPy) 2 ] 2 IJ2-propanol)} n (3) and {[ZnIJ1) 2 IJBipy) 2 ]IJDMF) 2 } n (4), incorporating halogen-bond (XB) donor sites and azobenzene groups have been synthesized and fully characterized.Obtaining 3 and 4 confirms that it is possible to use a ligand wherein its coordination bond acceptor sites and XB donor sites are on the same molecular scaffold (i.e., an aromatic ring) without interfering with each other. We demonstrate that XBs play a fundamental role in the architectures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is reported that 2,2 0 -dipyridyl decreases the reaction rate of Cu 2+ reduction via the adsorption on the Cu surface. [40][41][42] The contribution of 8.5 kJ mol À1 to k g is about 33% decrease in the reaction rate, indicating that the adsorbed 2,2 0dipyridyl on Cu also affect the pre-exponential factor that contains the collision rate of Cu 2+ on the Cu surface and a steric factor (proper orientation of the collision for the reaction).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that 2,2 0 -dipyridyl decreases the reaction rate of Cu 2+ reduction via the adsorption on the Cu surface. [40][41][42] The contribution of 8.5 kJ mol À1 to k g is about 33% decrease in the reaction rate, indicating that the adsorbed 2,2 0dipyridyl on Cu also affect the pre-exponential factor that contains the collision rate of Cu 2+ on the Cu surface and a steric factor (proper orientation of the collision for the reaction).…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, halogen bonds have emerged as an important tool in several fields of science and the understanding of these interactions has produced many contributions to materials science, organic, medical, and biochemistry fields. For instance, investigating the mechanism of ligand–protein interactions via halogen bonds and its influence on structural parameters of the ligand/protein complex can be a crucial factor to preview and design more efficient lead-molecules. …”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the presence of sterically unhindered bromine atom in CP‐1 which led to the delocalized C−Br⋅⋅⋅π type halogen bonding and long range ordered H‐type π‐π stacking that stabilized the triplet excited state for long‐lasting room temperature phosphorescence and created large electron pathways for efficient charge transport. Halogen bonding has also been successfully employed in influencing the supramolecular 2D layer formation in azobenzene‐functionalized Zn(II)‐based coordination networks [125] …”
Section: Halogen Bonded Supramolecular Polymers and Materialsmentioning
confidence: 99%